Technology, augmentation, and predicting the future of work - Dhondt, Steven (Henry Stewart Talks, 2022)
Digital Transformation, Predictions About the Future of Work, The Substitution Theory vs. The Augmentation Theory, Controlling Digital Technologies, Industry 5.0